Sustainable Banking and Credit Market Segmentation - David L. Kelly; Christopher Paik (CESifo GmbH, 2024)
We assess the feasibility, optimality, and policy implications of Environmental, Social, and Corporate Governance (ESG)-linked or "green" lending in a credit market where banks incorporate such non-financial data in credit allocation decisions. We identify an asymmetric information problem: borrowers signal low financial risk to banks who are uncertain about borrower risk levels by engaging in green investments. We derive conditions under which banks segment the market into green and brown loan products and evaluate market efficiency. We find borrowers prioritize signaling over the environmental impact of green investments, and the market sustains only limited green lending, since if all borrowers make green investments, no signaling value exists. The optimal carbon tax policy replaces the signaling value of green investments with the marginal damage and outperforms a brown reserve requirement aimed at discouraging brown lending. However, both policies also can sustain only a limited amount of green investments. We conclude that while green lending by banks can enhance welfare relative to an unregulated market, the resulting market segmentation can make the social optimum infeasible, even with carbon tax regulation.
Keywords: D80; D81; Q54; Q56; Q58; G21; E58; 330; competitive screening; ESG; environmental risk; climate risk; sustainable banking; sustainable finance; stranded assets